Saturday

August 23, 2014

August 23, 2014

Posted by **lil** on Wednesday, September 27, 2006 at 3:54pm.

You're supposed to treat y as a function of x and differentiate it implicitly. We have

d/dx{sinx- cosy)=d/dx{sinx) - d/dx{cosy)=

cos(x)-(-sin(y)*y')=0

You should be able to solve for y'.

I did, and I ended up with y'=-cos(x)/sin(y)

How do I simplify this further?

That's as far as you can go unless you know something specific about y. Without knowing something about y(x) there's nothing else to do here.

**Related Questions**

trig - Okay, I've been getting some of these, but I can't seem to verify this ...

Trigonometry Help - Simplify: sin(x-y)cosy+cos(x-y)siny = (sinxcosy-cosxsiny)...

Trigonometry - Prove that (cosy/1+siny) + (1+siny/cosy) = 2secy

math - sinx+ siny/ (cosx+cosy)= tan 1/2 (x+y) prove this identity

Trigo help! - Ok, i've tried this question, and it brings me to no answers. ...

Trigonometry - If Hello, I have been working on this one problem for a while now...

calculus - Could someone check my reasoning? thanx Find the derivative of the ...

precalculus - Given f(x)=x^2 -3x, find f(2x) in simplest form. so i got that you...

maths (trigonometry) - please solve these if possible Q1. If sinx +siny=3(cosy-...

Math help again - cos(3π/4+x) + sin (3π/4 -x) = 0 = cos(3π/4)cosx...